O discurso e a atividade: uma análise do trabalho do(a) fonoaudiólogo(a) com pais de crianças com perda auditiva - Tadros, Taís Olivetti Ferreira (2006)
This work aims to make reflections about a speech therapy professional activity with parents. This activity was concepted by the researcher and a speech therapist, offered during a week, for a discussion group in which, the speech therapist was responsible to conduct the discussion between parents of deaf children, whom are attended by Derdic (Divisão de Educação e Reabilitação dos Distúrbios da Comunicação) at the Pontifícia Universidade Católica de São Paulo (PUC-SP). The date was composed with an oral text produced during the application of an adaptation to the simple auto-confrontation method (Faïta, 1997), in which there were three steps: a) audio and video records of three meetings between these parents and the speech therapist. The film Mr. Holland-adorável professor, was showed for the parents, in the first meeting, to be discussed in the two others meetings; b) the edition of this recorder was made by the researched; c) an presentation of this edition to the speech therapist and this part of the research is the analyses material. The analyses are based on conceptual enunciative-discourse, specially, the conceptions by studies of Bakhtin/Volochinov (1929/1992), Bakhtin (1984/1992) and Maingueneau (1998/2004), and this conceptions are articulated with the knowledge of Ergologia (Schwartz, 1996, 1998, 2000, 2004) and Clínica da Atividade (Clot et al. 2000, 2001; Faïta, 1997, 2002, 2004, 2005). So, the reported speech is analyzed with the reflections about the uso das pessoas conception (Benveniste, 1966/2005), specially, the use of personal pronouns and the references. To the organization of the results, there are two topics: first, the words that meaning is related with the difficulties of the work with parents and, in the other side, the importance of this work which is related with the information to parents about the deaf and the importance of the speech therapist action in giving attention to the parents. The results showed, from the Language Sciences and Work Sciences notions, that, there is an activity genre of the speech therapy work with parents. So, from the dialogue between scientific publications about these issues and the results of this research, it was possible to do reflections about the issues that the speech therapist emphasized during the application of auto-confrontation method